DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE QUALIFIED WORKERS IN THE SERVICE SECTOR UNDER EDUCATIONAL TRANSFORMATIONS - Herlyand, Tetiana (Professional Pedagogics, 2023)
Relevance: In the context of reforming contemporary Ukrainian education and transitioning to multilevel training of professional staff, the competitiveness of specialists in the labor market, the problem of a competency-based approach becomes particularly relevant. In turn, the professional competence of future qualified workers in the service sector is an integral characteristic that determines the individual’s ability to solve typical professional tasks and problems that arise in real-life professional situations by using acquired knowledge and skills, professional and personal experience, values, and inclinations from a specific profession in the service industry. Objective: To analyze approaches to defining the essence and content of the definition "professional competence of future qualified workers in the service sector" in the context of modern educational transformations. Methods: Theoretical: analysis, synthesis, generalization of scientific works on the problem of professional competence of future qualified workers in vocational (vocational-technical) education institutions and official documents - to determine the theoretical-methodological foundations of the phenomenon; study and generalization of pedagogical experience to select pedagogical tools - for the development of professional competence of future qualified workers in the service sector; comparison - to determine approaches to solving the researched problem; modeling - to design a model for the development of professional competence of future qualified workers in the service sector during professional training. Results: The essence and content of the definition "professional competence of future qualified workers in the service sector" were examined; various scientific approaches to defining the concept of professional competence and its components were identified and analyzed; various scientific approaches to the classification of structural elements of the professional competence of a future specialist were characterized, which can be used to determine their competitiveness in the market and ensure their success in the service industry. Conclusions: It is recognized that professional competence acts as an indicator of the internal, subjective content of personality, is the result of purposeful internal work, its individual professional characteristic, in the process of which the external is processed and assimilated by the personality, generating a conscious ability to solve a specific professional problem and task in a particular situation, the ability to self-improve in one’s work; approaches to defining the essence and content of the definition "professional competence of future qualified workers in the service sector" in the context of modern educational transformations were substantiated (personality-oriented; systemic; activity-based; competency-based, integrated).